A highly selective and sensitive turn‐on fluorescent probe for the detection of Al3+ and its bioimaging. (13th December 2016) - Wang, Qingming; Yang, Lei; Wang, Hua; Song, Jialiang; Ding, Hui; Tang, Xin‐Hui; Yao, Hongmiao
Abstract: A novel fluorescent sensor, 1‐((2‐hydroxynaphthalen‐1‐yl)methylene)urea ( ocn ) has been designed and applied as a highly selective and sensitive fluorescent probe for recognition of Al 3 + in Tris–HCl (pH = 7.20) solution. The probe ocn exhibits an excellent selectivity to Al 3 + over other examined metal ions, anions and amino acids with a prominent fluorescence 'turn‐on' at 438 nm. ocn binds to Al 3 + with a 2:1 binding stoichiometry and the detection limit was 0.3 μM. Furthermore, its capability of biological application was evaluated and the results showed that the sensor could be used to detect Al 3 + in living cells.